De la voix au théâtre au théâtre de la voix : l’envers du décor poétique de Robert Browning - Yann Tholoniat (Cahiers Victoriens et Edouardiens)
Robert Browning wrote seven plays : Strafford, King Victor and King Charles, The Return of the Druses, A Blot in the ‘Scutcheon, Colombe’s Birthday, Luria and A Soul’s Tragedy. Over a decade, between 1836 and 1846, and despite failures that would have been daunting for anyone, the young poet strove to write for the stage. So far research on this topic has been scant. But Browning had actually intended to write for the stage from the start. Although these plays have remained « backstage » when one considers Browning’s achievement, they offer major insights into his research and his technique as far as staging voices is concerned. The scenes are midway between both text and stage directions, between the text and what is beyond the text, and they display a great variety of expression to such an extent that they constitute Browning’s poetics workshop for Dramatic Lyrics (1842) and Dramatic Romances and Lyrics (1845).